Axial neck pain: a surgeon''s perspective. Issue 6 (November 2011) - Clarke, Michelle J; Schiefer, Terry K; Pichelmann, Mark A; Krauss, William E
Neck pain is a common and difficult patient complaint. In the majority of cases, conservative treatment, including the use of pain medication, anti-inflammatories, rest, physical therapy and select injections provide the best relief of chronic pain. By elucidating the primary pain generator clinicians may be guided towards the best treatment options. Surgical treatment of axial neck pain is controversial and reported outcomes are not encouraging, with the exception of a select group of patients. This article is intended to provide the general clinician with an understanding of neck pain from a surgeon''s standpoint so that the treating physician can guide their patient''s expectations in advance of a surgical consultation. We have performed an extensive review of the English language literature discussing axial neck pain with a special focus on surgical treatment options. In addition, we give our opinion regarding both the conservative and surgical treatment of these challenging patients based on our own experience.